Adherence and virologic outcomes among treatment-naïve veteran patients with human immunodeficiency virus type 1 infection. Issue 2 (January 2018) - Cheng, Yan; Sauer, Brian; Zhang, Yue; Nickman, Nancy A.; Jamjian, Christine; Stevens, Vanessa; LaFleur, Joanne
Abstract : Abstract: Many studies have estimated the association between the adherence to antiretroviral therapies and human immunodeficiency virus (HIV) patients' virologic/immunologic outcomes. However, evidence is lacking on the causal effect of adherence on the outcomes. The goal of this study is to understand whether near perfect adherence is necessary to achieve optimal virologic outcome and also to investigate the effect of initial adherence to antiretroviral therapies on initial viral suppression by different regimens. A cohort study was conducted on HIV veterans initiating antiretroviral therapies in 1999 to 2015. The primary outcome was the first viral suppression occurred within 30 to 60 days since the index date. Multiple imputation was used to impute the missing value of virologic outcomes. The inverse probability of treatment weighting (IPTW) method was applied to estimate the viral suppression rate at each specific adherence category for each regimen category. Marginal structural models with IPTW were used to estimate the risk of viral suppression in lower-adherence categories in comparison to near-perfect adherence level ≥95%. Data showed that lower adherence caused lower viral suppression rate, with the association differentiated by the regimen. Patients on integrase strand transfer had the highest viral suppression rate, with patients on protease inhibitors having the lowest rate. Regardless of regimens, the viral suppression rate among patients at initial adherence of 75 to <95% was not statistically different from patients at adherence of ≥95%; however, the differences might be clinically significant. Abstract : Supplemental Digital Content is available in the text